The response of quadrangular plates to buried encased charges - Warncke, Dale (Department of Mechanical Engineering, 2019)
This dissertation reports on a series of experiments and numerical simulations that were carried out to investigate the response of quadrangular plates to buried encased charges with a view of understanding landmine effects on simple structures. Different loading scenarios were carried out for comparison. In total, four loading scenarios were investigated; namely bare and encased charges detonated in air, and bare and encased charges detonated under sand. A vertical pendulum was used to measure the impulse imparted onto the target plates, and dry construction sand was used to bury the charges. The geometric scaling of the target plates and PE4 explosive charge was based on the Casspir APC and TM-57 Anti-tank mine respectively. The experiments were carried out under varying conditions, such as different standoff distances (50-90 mm) and depths of burial (0-10 mm). In general, the impulse and midpoint deflection decreased with an increase in total distance for all loading scenarios. Burn diameters were observed on plates loaded in air, with dissimilar scorch areas observed on plates subjected to buried charges. Scorched areas on plates subjected to encased charges indicated a focussing effect of the explosive products provided by the charge casing. Plates subjected to encased charges detonated in air typically resulted in ’capping’ in the central area, accompanied by significant shrapnel damage. In general, presence of a charge casing in buried charge tests resulted in more damage to the target plate. Larger impulses and midpoint deflections were measured for charges detonated under sand compared to bare charges detonated in air. Encased charges detonated under sand resulted in decreased impulse imparted onto the target plate, accompanied by an increased plate midpoint deflection when compared to bare charges detonated under sand. The presence of sand in encased charge tests tended to mitigate the shrapnel damage caused by the charge casing. ANSYS AUTODYN was used to perform numerical simulations on three variable standoff distance test series, one with no sand and a bare charge, one with a constant depth of burial and a bare charge, and the last with a constant depth of burial and an encased charge. These simulations mirrored the experimental test series. The simulations consisted of two-dimensional axisymmetric models, with lagrangian meshes representing the target plate and explosive casing, and an eulerian mesh used to model the behaviour of the PE4, sand and air. The blast was simulated in two phases, namely detonation of the explosive and loading of the structure. The casing mesh was only included in the detonation phase. Two separate models were used to simulate the impulse and the plate behaviour. The impulse model used a reflective boundary to represent the plate and pressure histories on the reflective boundary were used to calculate the impulse. The plate loading model included a lagrangian mesh to represent the plate and simulate its deformation. The plate loading model used and additional unloading phase to allow plate oscillations to subside. The numerical model was validated using the impulse, plate midpoint deflection and plate profile measured during the experiments. The numerical model showed good correlation with the results of the experiments in terms of midpoint deflections and impulse trends. The model provided insights into the experiments, such as how the gas products expanded after detonation and their interaction with the target plate.